حِفْظُ القُرْآنِ الكَرِيمِ وَأَثَرُهُ فِي لُغَةِ الطِّفْلِ - Salem bin Ghormallah Alzahrani (مجلة كلية التربية للبنات, 2019)
In this age – in which dangers have raided language eloquence and statement - the Quran remains the greatest preservence of the sound language, and the greatest supporter for its people to preserve its richness and eloquence. It remains with it, as the night and day remain. This study revolves around the preservation of the Holy Quran and its impact on the language of the child. It consists of an introduction which includes the importance of the subject, the research plan, and methodology, and three sections. The first one is about the virtue of memorizing the Quran, and the benefits of memorizing it in general, and the second section deals with the impact of memorizing the Quran in the language of the child. It is represented in the following manifestations: - Tasting beautiful speech, - The integrity of pronunciation and eloquence of the tongue, - The integrity of the expression, - Verbal richness and eloquence of expression, - Proficiency in reading and writing. The third section is about the practical steps to nurture the language of the child by memorizing the Holy Quran, including: - Graduation in the teaching and memorization of the Quran, - Repetition and revision, - Understanding the verses and the statement of what is strange, -Then the conclusion, and the most important results, and finally the index of sources and references.